A Fully Coupled Hydromechanical Model for CO2 Sequestration in Coal Seam: the Roles of Multiphase Flow and Gas Dynamic Diffusion on Fluid Transfer and Coal Behavior. (24th September 2020) - Yang, Rui; Liu, Weiqun; Ma, Tianran; Xie, Junhe; Hu, Yang; Zhou, Rui; Yang, Yongjie
Abstract : CO2 sequestration in coal seam has proved to be an effective way for reducing air pollution caused by greenhouse gases. A study on the rules of fluid transfer and reliability of CO2 storage during gas injection is necessary for the engineering application. However, the clarification of multifield coupling in long-term CO2 sequestration is the difficulty to solve the aforementioned problem. Previous investigations on the coupled model for CO2 storage in coal seam were not exactly comprehensive; for example, the multiphase flow in the fracture and the nonlinear behavior of gas diffusion were generally neglected. In this paper, a new multistage pore model of the coal matrix and the corresponding dynamic diffusion model were adopted. Meanwhile, the CO2 -induced coal softening and the CO2 -water two-phase flow in coal fracture were also taken into account. Subsequently, all the mentioned mechanisms and interactions were embedded into the coupled hydromechanical model, and this new fully coupled model was well verified by a set of experimental data. Additionally, through the model application for long-term CO2 sequestration, we found that the stored CO2 molecules are mainly in an adsorbed state at the early injection stage, while with the continuous injection of gas, the stored CO2 molecules are mainly in a free state. Finally, the roles of multiphase flow and gas dynamic diffusion on fluid transfer and coal behavior were analyzed. The results showed that the impact of multiphase flow is principally embodied in the area adjacent to the injection well and the coal seam with lower initial water saturation is more reliable for CO2 sequestration, while the impact of gas dynamic diffusion is principally embodied in the area far away from the injection well, and it is safer for CO2 sequestration in coal seam with greater attenuation coefficient of CO2 diffusion.